Design and Implementation of Unmanned Autonomous Armed Cart Used for Military Purposes (University of Thi-Qar Journal for Engineering Sciences, 2018)
the save of soldier’s life in battlefield is an important thing in any battle plan. One of the solutions to economize the numbers of losses of soldiers’ life’s, is to use unmanned autonomous cart to perform some deadly functions in place of soldiers. This research proposes unmanned armed cart to support Iraqi army operations and to protect the soldiers from the snipers deadly shooting and from the explosion of mines. The proposed cart is armored and moving on four wheels. It is armed with machine gun and supplied with camera. All the commands of operations were performed using Programmable Logic Controller "PLC". The experimental performance passed successfully by the use of remote control.